Does CEO Managerial Ability Impacts on Corporate Investment Decisions? The Case of Economic Uncertainty in Political Election Periods - Iman Harymawan; Surya Patra Abdillah; Mohammad Nasih; John Nowland; Suham Cahyono (Asian Journal of Business and Accounting, 2024)
Manuscript type: Research paper Research aims: The objective of this study is to investigate whether CEO managerial ability has an effect on corporate investment decisions, particularly during the presidential election period as moderating role on this nexus. Design/Methodology/Approach: This research uses a quantitative approach to obtain empirical evidence whether CEO managerial ability affects corporate investment decisions. This research uses a sample of 2,962 firm-year observations of Indonesia-listed firms from the years 2010 to 2020. To obtain our research objectives, we used OLS analysis with STATA 17.0 Research findings: This study found that CEOs’ managerial ability has a significant and positive effect on the firm's investment decision. The authors further address potential endogeneity and check the robustness, use methods including coarsened exact matching and instrument variable approach using Heckman (1976) two-stage least square. Theoretical contribution/Originality: The research explores the moderating role of CEO ability in the context of election-induced uncertainty and investment decisions. It could contribute to the understanding of how CEO capabilities influence strategic choices under uncertain conditions. Research implications: This research contributes to the existing literature on the various impacts of CEO managerial ability on firm outcomes. The research also encourages policymakers and regulators to prioritise the development and retention of talented managers to ensure the financial and economic stability of Indonesian firms, particularly during periods of financial distress.